Keratoacanthoma: Update on the Debate. (April 2021) - Nirenberg, Alexander; Steinman, Howard; Dixon, Anthony
Abstract : Abstract: Keratoacanthoma (KA) is a cutaneous tumor with a biphasic pattern of growth. A rapidly growing phase is usually followed by involution. KA occurs on sun-damaged skin. There are many listed causative associations, which include some therapeutic agents. Debate continues as to whether KA is a variant of squamous carcinoma (SCC) or a separate entity. Reporting of KA versus SCC is markedly inconsistent. Reasons for inconsistency include overlapping microscopic criteria, variants of KA with more aggressive features, and possibly medicolegal concerns. Genetic studies have shown some differences between the 2 entities. Activation of apoptotic pathways has been demonstrated in KA. Genetic studies have shown a possible role of human polyomavirus 6 in the pathogenesis of at least some KAs. Given that some cases of KA have components that behave as conventional SCCs, KA can be considered as a low-grade variant of SCC with some genetic differences.